Effect of AR (2) Model on the Economic Design Mean Chart with Known Coefficient of Variation Under Non Normal Population - Singh, JR; Sanvalia, A (International Journal of Computer Sciences and Engineering, 2025)
In this paper, we have studied the effect of AR (2) model and non-normality on the economic design of mean chart with known coefficient of variation under non normal population. We use the first four terms of an Edgeworth series for the production cycle time and cost parts. In AR (2) model three different situations arise as (i) Roots are real and distinct (ii) Roots are real and equal (iii) Roots are complex conjugate. The significant effects are seen on mean chart for the above three situation. We also develop the formula for the sample size (n) and sampling interval (h) for different combination of the skewness and kurtosis under AR (2) model.